Effects of Black Tea on Salivary pH and Flow Rate - DMD, Peiman Shalal, (International Journal of Innovative Research in Medical Science, 2017)
Saliva is the mouth’s main defense against tooth decay, keeping the mouth’s tissues healthy and offering protection from microbial invasion that can lead to disease. The present study was undertaken with the aim of assessing the effect of black tea on salivary pH and flow rate amongst 255 healthy adults between the ages of 25 and 30. Saliva samples were collected before and after consumption of black tea for 3 minutes. The changes in the unstimulated and stimulated saliva were monitored by measuring the flow rate with a measuring cup that was weighed in a precision balance while the salivary pH was measured with a digital pH meter. A paired t-test was used to analyze results. Both salivary flow rate and pH level results were statistically significant (p≤0.05) with a p-value of (p =0.013) for flow rate and a value of (p =0.0004) for pH level after consumption of black tea. Study shows that black tea significantly increases the pH level and flow rate of saliva.